Oral form discrimination skill as a function of age and sex in children - Shalini (Journal of All India Institute of Speech and Hearing)
Oral form discrimination skill in ’even age’ group children ranging in age from 6 to 12 years was tested to determine the developmental trend and sex difference in them. Forty-eight school-going children with Kannada as mother tongue were chosen after administering the screening tests. Children were grouped under four age groups, 6, 8, 10 and 12, with each group consisting equal number of boys and girls.